Leadership in Utopia and Dystopia: A Comparative Study of Plato and Machiavelli - Hamid, Asma (Al-Irfan, 2023)
Plato and Machiavelli are two important figures in the history of political thought. Regarding the concept of leadership, the views of both thinkers have been discussed in every age. Although the two thinkers have different positions on the concept of leadership, there is agreement between the two thinkers on some points. Plato talks about the philosopher king, who is a figure of wisdom and high moral values. Philosopher King constructs state and society according to high values based on these same high qualities. Plato’s state is called Utopia. This state is difficult to establish in real life. Regarding morality and human nature, Plato has a positive point of view to such an extent that the Philosopher King makes the entire society a figure of moral values. Plato’s Philosopher King emphasizes the internal affairs of the state and the maintenance of the moral force of society more than the external affairs. Unlike Plato, Machiavelli formulates his political thought keeping in view the practical facts of life. His prince is a ruler with the ability to solve real political problems. He focuses on the stability of the state, solving the problems of the people, providing them with a better living environment and security, even if he has to compromise on moral values. Machiavelli does not think it is bad to sacrifice religion, moral values and women for political purposes and stability of the state. Machiavelli’s prince is not limited to internal affairs only, but his focus is also on the external affairs of the state. Contemporary political leadership can also be understood according to Plato and Machiavelli’s concepts of leadership.